Corrupting Capitalism: Michael Ende’s Momo and “Cathedral Station” - Heike Polster (Studies in 20th & 21st Century Literature, 2016)
Michael Ende, the well-known author of The Neverending Story, foresaw dramatic changes in the fabric of society resulting from a turn toward neoliberal policies. One such far-reaching and dangerous change has to do with a diminishing of temporal autonomy, the ability to freely determine the use and meaning of our time. This article explores how neoliberalism is shaping our concept of time and our experience of it. In an effort to demonstrate the process and the line of reasoning behind the monetization of time, and to connect time to more qualitative considerations of the human condition, I shall demonstrate how Ende conceptualizes time as an integral part of the accumulation process of capitalism. I also discuss a fairly cryptic short story, “Cathedral Station,” that envisions “the mystery of money.” Utilizing Walter Benjamin’s critique issued in his 1921 fragment “Capitalism as Religion,” I outline Ende’s dystopian vision of the uncontested, unquestioned reign of capitalism as a religious cult. Read together, the novel and the short story offer a way of contrasting two extreme byproducts of capitalism’s colonization of time, namely what I would call an “ideology of work” and an “ideology of growth.” The first of these is a result of capitalism’s commodification of time according to liberal ideals such as choice, freedom, and self-interest. The second is a decidedly neoliberal phenomenon in that the “financialization of everything,” to use David Harvey’s phrase, results in the ever-present expectation of unlimited, exponential growth. By drawing out these two interconnected ideologies through close readings, the subtle processes of capitalism’s colonization of time are revealed.
Keywords: neoliberalism; capitalism; Michael Ende; time; ideology; work